Thermodynamic behaviour of nitrogen in the carbon saturated Fe-Mn-Si alloy during casting. (2nd September 2020) - Paek, Min-Kyu; Jeon, Junmo; Lindberg, Daniel
ABSTRACT: The evolution of nitrogen gas formation in cast iron was studied based on the information of the N solubility in the carbon-saturated iron-containing Mn and Si over the wide temperature range. In order to verify the accuracy of the Fe-Mn-Si-C phase diagram, the transition temperatures of the Fe-Mn-2.7 wt%Si-Csat alloys were measured according to the Mn concentration using a differential scanning calorimetry under the purified Ar atmosphere. The recent thermodynamic modelling result of the Fe-Mn-Si-C-N system was used to describe the solubility limit of N in liquid and solid solution in the carbon saturated iron alloys. The cooling and quenching experiments were also carried out to check the effects of temperature and phase transformation on the N solubility limit in the temperature range from 500°C to 900°C.